Hospital Acquired Bacterial Infection in Burns Unit at Cipto Mangunkusumo Hospital, Jakarta - PRATIWI SUDARMONO; VERONICA WIWING (Microbiology Indonesia, 2007)
Burn injury causes mechanical disruption to the skin, which allows environmental microbes to invade the deeper tissues. A prospective study of infections in burn patients has shown that the incidence of hospital acquired bacterial infection in burn wounds was high. In the Burns Unit, Cipto Mangunkusumo Hospital, Jakarta, 94 patients were hospitalized from January to July 2004. The objective of this study was to evaluate the hospital acquired infections in burn wounds. Using a cross sectional study, 49 patients were included. The specimens for bacterial investigation were obtained from clean eschar which has healthy tissue taken at day 1, day 5 and day 10. At the same time, bacterial investigations were conducted from the air and the water, as well as from the hand and nasal swabs of hospital personnel. The results show that Klebsiella pneumoniae is the most prominent bacterium found in the wounds, but it is also found in the air. Pseudomonas aeruginosa was the number two causative bacteria which caused a change of the bacterial infectivity on day 5 and 10. These bacteria were always found when we conducted bacterial investigations from the water resource of the burns unit. Methicillin Resistant Staphylococcus aureus is also found in the nasal swab of hospital personnel. Using the antibiogram pattern, there were similarities between bacteria found in the wounds and in bacteria found in the air and water. In conclusion, hospital acquired burn wound infection in Burns Unit, Cipto Mangunkusumo Hospital is as high as 62%. The surveillance data are very important for developing good clinical practice guidelines in burn injury treatment and management